Impact of Severe Sarcopenia on Rehospitalization and Survival One Year After a TAVR Procedure in Patients Aged 75 and Older - Brouessard C (Dove Medical Press, 2021)
Céline Brouessard,1 Anne Sophie Bobet,1 Marie Mathieu,1 Thibaut Manigold,2 Pierre Paul Arrigoni,3 Thierry Le Tourneau,4 Laure De Decker,1 Anne-Sophie Boureau1,4 1Department of Geriatrics, University Hospital, Nantes, France; 2Department of Cardiology, Institut du Thorax, University Hospital, Nantes, France; 3Department of Radiology, University Hospital, Nantes, France; 4Université de Nantes, CHU Nantes, CNRS, INSERM, Institut du Thorax, Nantes, F-44000, FranceCorrespondence: Anne-Sophie BoureauDepartment of Geriatrics, University Hospital, Nantes, 44093, FranceTel +33 2 40165046Email annesophie.boureau@chu-nantes.frBackground: Transcatheter aortic-valve replacement (TAVR) reduces mortality and improves quality of life in patients with severe aortic valve stenosis. One third of patients have no benefit one year after TAVR. Sarcopenia, an age-related loss of skeletal muscle mass, is associated with increased physical disability and mortality. The main purpose was to evaluate the impact of severe sarcopenia on rehospitalization one year after TAVR in older patients.Methods: All patients aged ≥ 75 referred for a TAVR in 2018 were included. Severe sarcopenia was defined by a loss of skeletal muscle mass defined on CT-scan measurement associated with a gait speed ≤ 0.8m/s. The main outcome was rehospitalization one year after TAVR.Results: Median age of the 182 included patients was 84, and 35% had an unplanned hospitalization at one year. Severe sarcopenia was diagnosed in 9 patients (4.9%). Univariable analysis showed that gait speed was a factor associated with readmission [HR=0.32, 95% CI (0.10– 0.97), p=0.04] but not severe sarcopenia. In multivariable analysis, only diabetes was significantly associated with rehospitalization [HR=2.06, 95% CI (1.11– 3.84), p=0.02]. Prevalence of severe sarcopenia varied according to different thresholds of skeletal muscle mass on CT-scan.Conclusion: Even though severe sarcopenia was not correlated with rehospitalization and mortality at one year after TAVR, our results emphasize the changes in the prevalence according to cutoff used. It highlights the need to define standardized methods and international threshold for sarcopenia diagnosis by CT-scan measurements, in general population and for patients with valvular heart disease.Keywords: sarcopenia, older, aortic stenosis, transcatheter aortic valve replacement, hospitalization